International Dental Aid and WWII - Riaud, Xavier (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
During the liberation of the camps, a great majority of the detainees died after eating abundantly within a short period of time. A thousand men died because the Americans and the Englishmen were totally bewildered and overwhelmed with what was in front of them. In good faith, they gave a great amount of food to the survivors without thinking of the dramatic consequences that this was going to cause. Indeed, the survivors’ weakened bodies could not bear too much food. As a result, they changed their minds and they set up field hospitals which were to feed the sick through successive steps.